PENGARUH KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN DAN KEPUASAN NASABAH PADA KANTOR PEGADAIAN SYARIAH SUBRANTAS KOTA PEKANBARU - Allvin, Muhammad; Zulkarnain, Zulkarnain; Firli, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aimed to analyze the influence of Quality of Services To Purchase Decision and Customer Satisfaction in the Islamic pawnshop Subrantas Office Pekanbaru. In this study there is an independent variable that is Quality of Service (X), Purchase Decision (Y1) and Customer Satisfaction (Y2) as the dependent variable. This research was conducted in the area of Pekanbaru with the object of research is the Office of the Islamic pawnshop Subrantas Pekanbaru. The population of this research is the customer in the Office of the Islamic pawnshop Subrantas Pekanbaru City with a total sample of 120 people. Analysis using Path Analysis with SPSS version 21. The data used in this research is Quantitative and Qualitative Data. The results of this study indicate that the variable quality of service simultaneously and partially influence the purchase decision and Customer Satisfaction in the Islamic pawnshop Subrantas Office Pekanbaru. Variable quality of service to be the most dominant factor in influencing purchasing decisions and customer satisfaction. Hope researchers in this study is the best Office Pekanbaru City Subrantas Islamic pawnshop can improve Quality of Service so that it can continue to increase the purchase decision and Customer Satisfaction in the Islamic pawnshop Subrantas Office Pekanbaru.Keywords : Service, Customer Satisfaction and Purchase Decision